Cover crops and biocontrol agents in the management of nematodes in soybean crop - Araújo, Fernando Godinho de (2023)
In the Brazilian Cerrado, phytonematodes, phytonematodes are a challenge for agriculture, and the association of forms of control is the best strategy to be used in coexistence with this pathogen. Faced with this problem, this study aimed to evaluate the efficiency of cover crops and biocontrol agents in the management of nematodes in soybean. For each nematode species under study (Meloidogyne incognita and Pratylenchus brachyurus), two experiments were carried out under greenhouse conditions in a completely randomized design arranged in a 6 x 2 factorial scheme with eight replications. Six cover crops (millet ADRG 9050, millet ADR 300, Urochloa ruziziensis, Crotalaria ochroleuca, C. spectabilis, and corn hybrid DKB 290) and two treatments (treated or not with Bacillus subtilis and B. methylotrophicus - 1x106 CFU per seed) were evaluated. The cover crops were sown in soil infested with nematodes and then soybeans were sown under the straw, and cultivated for 45 and 60 days, for M. incognita and P. brachyurus, respectively. Fresh root mass, total nematode population, and the number of nematodes per gram of root were evaluated. The association of microorganisms with C. spectabilis, U. ruziziensis, and millet ADR 300 conferred an additional effect in reducing the population of P. brachyurus. For M. incognita, the association was successful only for combining C. spectabilis with B. methylotrophicus. DKB 290 corn, when treated with B. methylotrophicus, had the nematode population per gram of soybean root reduced by 90% compared to plants that did not receive biological treatment.